Respuesta :

Simplifying

12x + -18 = 90

Reorder the terms:

-18 + 12x = 90

Solving

-18 + 12x = 90

Solving for variable 'x'.

████████████████████████████████████████████

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.

-18 + 18 + 12x = 90 + 18

Combine like terms:

-18 + 18 = 0

0 + 12x = 90 + 18

12x = 90 + 18

Combine like terms:

90 + 18 = 108

12x = 108

Divide each side by '12'.

x = 9

Hence,

    x = 9

Hope this helps! <3

Ver imagen ImAGayBoy